Intrinsic dс Josephson effect in naturally layered stacked structures based on BSCCO 2212 single crystal whiskers - Latyshev, Yu.I.; Nevelskaya, J.E.; Monceau, P. (Физика низких температур, 1996)
The dependences of the critical current Ic across the layers on a parallel magnetic field H have been studied on small area stacked junctions fabricated from perfect single crystal whiskers. The intrinsic de Josephson effect has been clearly demonstrated on structures with in-plane size L less than 20μm. A dimensional crossover to monotonic size-independent behavior of Ic(H) has been observed with increase in L. The decrease of Ic(H) in this region is proportional to the square root of H in accordance with Fistul-Guliani theory.